BIMSTEC master plan for transport connectivity. (Metro Manila, Philippines Asian Development Bank, 2022)
It is intended to guide actions and promote synergies among various connectivity frameworks and help achieve sustainable development of the region. A specific framework is presented here for organizing a set of policies, strategies, and projects toward realizing a shared vision of peace, prosperity, and sustainability. With BIMSTEC’s unique geographical position as a bridge linking South and Southeast Asia, this document is also relevant to its neighboring regions. BIMSTEC was established as a regional organization in June 1997 to promote free trade within the region, increase cross-border investment and tourism, and promote technical cooperation.
Executive Summary - - Introduction and Background - - Overall Master Plan Framework - - Roads and Road Transport - - Railways and Rail Transport - - Ports and Maritime Transport - - Inland Water Transport - - Civil Aviation and Airport Development - - Multimodal and Intermodal Transport - - Trade Facilitation - - Human Resource Development - - Implementation - - Appendixes.
Keywords: Transportation; Transportation -- Southeast Asia; Electronic books